If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6=2(n+2)
We move all terms to the left:
6-(2(n+2))=0
We calculate terms in parentheses: -(2(n+2)), so:We get rid of parentheses
2(n+2)
We multiply parentheses
2n+4
Back to the equation:
-(2n+4)
-2n-4+6=0
We add all the numbers together, and all the variables
-2n+2=0
We move all terms containing n to the left, all other terms to the right
-2n=-2
n=-2/-2
n=1
| (15/3)*(4+1)=v+5 | | 10x+5=7x+8=8x-1 | | 180=5x+11 | | 52=m+1 | | 0.7(10x+16)=3.4(0.2x+5) | | 6/13=5/13+p | | (15|3)*(4+1)=v+5 | | 25n=125 | | 9+c=14 | | -7-7x+7x=-119 | | d+6=0 | | n-4.2=4.7 | | 4+e=1 | | 7k–8=6 | | 7k–8 = 6 | | -4=2n+2+n | | -4x2-(-2)=^2-3)^3= | | 6u+10=8u+4 | | 1/2x-3/4=1/4x+9 | | 28-7x=3x | | 7/12b=1 | | 5x+12+2x+14=77 | | 50=600f | | 50-9x=77 | | 1.1x+.35=-8.1 | | 8/3z=-9+7 | | -1a-3=-1a-1-2 | | 20=-10m-3 | | y=5(9)+10 | | -7-7x+7=-119 | | 3x=33x= | | 21+2.5w=6=5.7w-3.2w+15 |